Caracterização morfológica e sedimentar do talude continental (foz do Amazonas) - Souza, Danielle Cristina Costa de (2010)
Created on 3 december 1997, the REMPLAC (Program for Assessment of Mineral Potencial of the Continental Shelf), this porgram aimed to make the basic survey, systematic geological and geophysical continental shelf, detail, at an appropriate scale, sites geo-economic, and perform the analysis and evaluation of mineral deposits. The REMPLAC should continue the efforts of Global Recognition Program of the Brazilian Continental Margin REMAC closed in 1978, the operations Geophysical Sea (GEOMAR) developed by the Directorate of Hydrography and Navigation and the various initiatives of the Program of Marine Geology and Geophysics (PGGM). Despite the high interest on the Amazon platform, there is little information o their morphology and sediment characterization, and in order to fill this gap, the present work samples sedimentological point followed by seismic acquisition. And the studies were to characterize the possible area of interest as being directly influence by tides, which sediments are reworked throughout the platform featuring grain angle with sharp corners, and the carbonate content increases as it approaches the breakdown the platform, and the bodies found outside the foraminifera and mollusks. However, diverging with organic matter that reduces its concentration as it moves away from the coast. The seismic profiles do not get satisfactory results because of low visibility, however, to correlate with the spot samples, of sediment were possible morphological characterization of the area.